The Effect of Gamma Irradiation on Threshold Voltage and Channel Mobility Degradation of NMOS - Kerdpradist, Amonrat; Ruangphanit, Anucha; Titiroongruang, Wisut; Muanghlua, Rangson (My University, 2018)
This paper presents the effect of Gamma Irradiated on threshold voltage, surface mobility and transconductance on N-channel MOSFET devices at a gate oxide thickness of 15 nanometers, which is fabricated at Thai Microelectronics Center by 0.8-micron CMOS technology. Then gamma irradiation (Co-60) at a total dose varied from 1 to 10 \mathbf{kGy}. By performing five rounds to observe changes in threshold voltage when the devices were exposed to gamma rays for measurement to extraction threshold Voltage (VTH) into the surface mobility (Uo) from IDSVs VGs curves in the saturation region. As a result, the threshold Voltage reduces at highest dose by approximately 38% compared with conventional N-channel MOSFET, for a parameter extraction in the level 3 model for MOSFET SPICE parameters is presented.
Keywords: extraction Threshold Voltage; Gamma Irradiated; N-channel; surface mobility